(The Impact of Workforce Nationalization on Career Commitment (A Case Study on Saudi Geological Survey in Jeddah - Al Qutb, Hoda Ragheb; Ghaith, Nervana Abdulrahman (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aimed to reveal the impact of workforce nationalization on career commitment in Saudi Geological Survey (SGS) in Jeddah. The study shed the light on three main dimensions; the quality and the quantity of the nationalization besides analyzing the policies and practices of human resource management in Saudi Geological Survey. This study followed quantitative methodology. Data was collected via a structured questionnaire on 265 employees in Saudi Geological Survey (total employees number is 870). The sample was selected randomly within the organization. Software SPSS was used for data analysis. Results showed that nationalization achieved moderate levels in this organization. The ranking of the study dimensions – higher to lower levels – was: qualitative nationalization, quantities nationalization, policies and practices of human resource management. In terms of career commitment, data illustrated high levels of career commitment among Saudi Geological Survey employees. Thus, the study proved that there is a positive impact of workforce nationalization on career commitment in Saudi Geological Survey in Jeddah. This study recommend Saudi Geological Survey: a) to expand the nationalization to include more jobs in Saudi Geological Survey; b) to constantly improve human resources skills to increase their efficiency; c) to improve policies and practices of human resource management in complement with 2030 vision; d) to achieve employees justice; and e) to encourage employees who are commented to their work.
Keywords: job localization; job commitment; Saudization of jobs; Geological Survey Authority